Snapback‐free reverse conducting IGBT with p‐float and n‐ring surrounding trench‐collector. Issue 24 (3rd November 2020) - Li, Jie; Huang, Mingmin; Chen, Chang; Yang, Zhimei; Ma, Yao; Gong, Min
Abstract : A reverse conducting (RC) insulated gate bipolar transistor (IGBT) with p‐float and n‐ring surrounding trench‐collector is proposed. The p‐floats surrounding sidewalls of trench‐collectors suppress snapback and also avoid snapback when there are semiconductor/trench‐collector interface charges ( Q f ). The n‐rings surrounding the top of the trench‐collectors speed up the forward recovery and ensure a high breakdown voltage. Technology computer aided design (TCAD) simulations are carried out to compare the proposed RC‐IGBT and the RC‐IGBT with p‐poly trench‐collector (PTC RC‐IGBT). With Q f = 1 × 10 11 cm −2, the proposed RC‐IGBT is snapback‐free while the PTC RC‐IGBT has a snapback voltage of 4.43 V. The peak forward recovery voltage of the proposed RC‐IGBT (12 V) is much lower than that of the PTC RC‐IGBT (246 V). Besides, the reverse recovery charge of the two RC‐IGBTs is 48% lower than that of the PiN diode.